"Three Crossings" Compensations of the High Speed Moving MIMO Radar. (10th April 2014) - Luo, Cheng; He, Zishu
Abstract : The problems of the "Three Crossings" motions and compensations for the moving target of the high speed moving MIMO radar are studied. Firstly, the space model is established to describe the problems by educing the equations of delay and transmitting pattern, which are changing with time. The echo characteristics are analyzed and the formulas of the "Three Crossings" are given. Secondly, a compensation method, which uses the fractional Fourier transform (FrFT) to compensate the crossing Doppler-cell and the preprocess to compensate the crossing range-cell and crossing-beam, is proposed. This method could compensate the "Three Crossings" simultaneously with little complexity of calculation because the preprocess deals only with the transmitting signals. Lastly, the phantom antenna array is employed in the simulations, the working model of "sparse transmitting dense receiving" is applied to the simulation of crossing-beam, and the results of simulations demonstrate the validity and the practicability of the method of combining the preprocess and the FrFT to compensate "Three Crossings."